(untitled) (International Journal of Food and Nutritional Sciences, 2022)
And the Mountains Echoed is a novel about the interconnectedness of all human beings - it is no surprise that compassion is among the most important themes. At times, the characters make choices aiming to benefit only themselves, but at many other points they choose to help other people. Hosseini poses some complicated questions related to this theme: for which people do the most compassion for how long are we obligated to help these people and at what point does compassion become a kind of selfishness a way to fight one’s own sense of guilt.